Attribution styles associated with premenstrual syndrome in women at reproductive age, Iran - Salimeh Kord Firoozjaei; Mouloud Agajani Delavar; Ali Asghar Bayani (Babol University of Medical Sciences, 2015)
Background: Despite the fact that many research studies, concerning the premenstrual syndrome (PMS), have been conducted in recent years, the relationship between psychological and social factors with PMS remains controversial. The aim of the present study was to examine the association between attribution style in the PMS for positive and negative events. Methods: A total number of 241 employed women, with the age range of 20 to 40, were randomly selected for the sake of this study. An Attribution Style Questionnaire (ASQ) and a Delany's Premenstrual Checklist were completed by the participants during the follicular and luteal phases, respectively. Pearson correlation coefficient and regression were used for analyzing data.  Results: The PMS group included 145 women, who were experiencing moderate to severe PMS. According to the findings, the negative globality dimension was significantly associated with PMS (r= 0.16, P=0.011). No significant findings for the other attributional style scales were observed.  Conclusion: The results suggest that negative global attributional style appears to be an important construct in PMS therefore, it can be concluded that women with global attribution style for negative events are more likely to suffer from the PMS.